Rare chromosomal abnormalities: Can they be identified using conventional first trimester combined screening methods? - Daniel Kane; Mary E. D'Alton; Fergal D. Malone (Elsevier, 2021)
Objective: To evaluate the performance of first trimester combined screening for the detection of rare chromosomal abnormalities, other than Trisomies 21, 18 or 13 or 45 × . Study design: A database containing 36,254 pregnancies was analyzed. These patients were recruited at 15 US centers and included singleton pregnancies from 10 3/7-13 6/7 weeks. All patients had a nuchal translucency (NT) scan and those without a cystic hygroma (N = 36,120) underwent a combined first trimester screening test ('FTS' - NT, PAPP-A and fbHCG). A risk cut-off of 1:300, which was used for defining high risk for Trisomy 21, was also used to evaluate the detection rate for rare chromosomal abnormalities using the combined FTS test. Results: 36,120 patients underwent combined FTS. Of these, 123 were found to have one of the following chromosomal abnormalities: Trisomy 21, Trisomy 18, Trisomy 13 or Turner syndrome. This study focuses on 40 additional patients who were found to have 'other' rare chromosomal abnormalities such as triploidy, structural chromosomal abnormalities, sex chromosome abnormalities or unusual chromosomal abnormalities (e.g. 47XX + 16), giving an incidence of 1.1 in 1000 for these rare chromosomal abnormalities. Of these 40 pregnancies, only 2 (5%) had an NT measurement of ≥3 mm. The detection rate for combined FTS, using a risk cut-off of ≥1:300, was 35 % (14 of 40 cases). Therefore, 65 % of cases of rarer fetal chromosomal abnormalities had a 'normal' combined FTS risk (<1:300) and 95 % had a 'normal' NT (<3 mm). Conclusion: Traditional FTS methods are unable to identify the vast majority of rare chromosomal abnormalities. Our data do not support the potential detection of rare fetal chromosomal abnormalities as a reason to favour nuchal translucency-based first trimester screening over NIPT.